Scalability of Phase Change Materials in Nanostructure Template - Wei Zhang; Biyun L. Jackson; Ke Sun; Jae Young Lee; Shyh-Jer Huang; Hsin-Chieh Yu; Sheng-Po Chang; Shoou-Jinn Chang; Ya-Hong Xie (International Journal of Photoenergy)
The scalability of In2Se3, one of the phase change materials, is investigated. By depositing the material onto a nanopatterned substrate, individual In2Se3 nanoclusters are confined in the nanosize pits with well-defined shape and dimension permitting the systematic study of the ultimate scaling limit of its use as a phase change memory element. In2Se3 of progressively smaller volume is heated inside a transmission electron microscope operating in diffraction mode. The volume at which the amorphous-crystalline transition can no longer be observed is taken as the ultimate scaling limit, which is approximately 5 nm3 for In2Se3. The physics for the existence of scaling limit is discussed. Using phase change memory elements in memory hierarchy is believed to reduce its energy consumption because they consume zero leakage power in memory cells. Therefore, the phase change memory applications are of great importance in terms of energy saving.